Application of Constructivism Approach in the Learning of Initial Value Matter and Boundary Requirement Course - Elfis Suanto; Armis Armis (Journal of Educational Sciences, 2017)
The purpose of this research is to repair the mathematic learning process of Initial Value Matter and Boundary Requirement (IVMBR) course. The variables which have been examined (1) the activities of lecturer and students in learning process, (2) the development of student grades, and (3) the completeness of student result in studying of IVBVP. These actions have been done in three cycles based on data’s analysis, we get the result (1) the lecturer and students activities in learning process have been improved, (2) the development of student grades is rather the same in three of the cycles, and (3) the student who could reach the studying completely. After first cycle, these students get A or B increasing to 62,50,`4%, and after second cycle, the completeness of study has increased to 66,67%, and after third cycle, the completeness of studying have increased to 75,00%. Based on these informations, the constrctivism learning is good to use in learing of IVMBR course.